Coupling molybdenum carbide nanoparticles with N-doped carbon nanosheets as a high-efficiency electrocatalyst for hydrogen evolution reaction. (10th May 2018) - Zhou, Guangyao; Yang, Qian; Guo, Xiaomeng; Chen, Yang; Yang, Qian; Xu, Lin; Sun, Dongmei; Tang, Yawen
Abstract: Searching for earth-abundant and high-efficiency electrocatalysts for the hydrogen evolution reaction (HER) is of critical importance for future energy conversion devices. To facilitate the HER on a nonprecious metal-based catalyst, integration of catalytically active nanoparticles with highly conductive carbon supports represents a promising strategy since the formed nanohybrid can offer available active sites and improved electron transfer capability. Herein, we demonstrate a feasible and scalable approach to fabricate well-dispersed Mo2 C nanoparticles firmly anchored on 2D ultrathin N-doped carbon nanosheets (denoted as Mo2 C@NC nanosheets) using inexpensive NaCl as recyclable templates. The adoption of NaCl template provides a 2D space for the one-step concurrent growth of Mo2 C nanoparticles and N-doped carbon nanosheets. Benefiting from the synergy between fine Mo2 C nanoparticles with high dispersity and N-doped C nanosheets, the resultant Mo2 C@NC nanosheets exhibit an outstanding HER performance with a low overpotential, a small Tafel slope and excellent stability under acidic medium, making them a promising noble-metal-free HER catalyst. Graphical abstract: We report a facile pyrolysis approach to fabricate 2D ultrathin N-doped carbon nanosheets decorated with well-dispersed Mo2 C particles (denoted as Mo2 C@NC nanosheets) by using NaCl crystallites as templates. Benefiting from the unique structural and compositional advantages, the as-synthesized Mo2 C@NC nanosheets exhibit a low HER overpotential, a small Tafel slope and excellent stability under acidic condition. Highlights: Mo2 C nanoparticles are firmly anchored on 2D ultrathin N-doped carbon nanosheets. Inexpensive NaCl is used as recyclable template. NaCl template provides a 2D space for the growth of carbon nanosheets. The catalyst exhibits outstanding HER performance under acidic medium.